Ideology of Civil Society Organisations in Nigeria’s Democratization Process, Between Cynicism and Solidarity, 1999-2020 - LEO-NNOLI, Tobechukwu Chukwudifu; BIEREENU-NNABUGWU, Makodi (Socialscientia: Journal of Social Sciences and Humanities, 2021)
The docility of civil society organisations in Nigeria’s democratisation process has been critiqued on grounds of extremities of either anti-democratic and elitist objectives or being driven by local anti-government objectives. In particular, evidence from Enugu State government-owned newspaper in Nigeria; Daily Star, substantiated that, civil society organisations in the State were mostly rationalizers of the impulses of government, notoriously elitist as praise singers. We therefore posited that the historical dualism in organizational ideology of civil society organisations in Enugu State, in the imbalance between cynicism and solidarity is a challenge to the democratisation process. In doing this we asked: How did civil society organisations’ cynicism and solidarity ideologies significantly relate to the deepening of international democratic objectives in Enugu state, 1999-2020? The study made use of the Exploratory Research Design, using the Structural-Functional Analysis and the Post-Colonial State theory as frameworks for analysis. A Mixed Method of data collection and analysis was used, focusing on a sample of 312 respondents drawn from a population of 1434 members of civil society organisations. The study used the Multilinear Regression model in the Statistical Packages for the Social Sciences IBM(SPSS) version 20 to test the statistical hypothesis that: civil society organisations’ need for unity and welcoming local community partners are significantly related to deepening international democratic objective in Enugu State, 1999-2020. It was recommended that civil society organisations in Enugu State Nigeria need to balance their need for internal cohesion and unity with the welcoming of the community stakeholders as partners, thereby deepening the democratisation process in the state, especially, in the areas of good governance, gender equality, rule of law and constitutionalism.